Manajemen Komunikasi Krisis Era Transparansi Radikal: Integrasi Data Visual Real-Time sebagai Instrumen Restorasi Reputasi dalam Industri AMDK - Brilian Prabasari; Sindy Dwi Kurnia; Marjam Desma Rahadhini (Jurnal of Management and Social Sciences, 2026)
The phenomenon of radical transparency in the Bottled Drinking Water (AMDK) industry in 2025 triggered a reputation crisis and a massive erosion of customer loyalty. This crisis began with negative sentiment on social media that led to surprise inspections by regulatory authorities of the industry leader's "Mountain Spring" claim. The unpreparedness of the communication infrastructure in presenting technical data in real time led to a decline in brand image and a significant correction in market share to a critical figure of 47.4%. This article aims to formulate a conceptual framework for adaptive and data-driven PR presentation techniques through the integration of real-time data visualization and narrative reframing strategies. The method used is a descriptive conceptual analysis by evaluating the chronology of incidents and PR responses during the crisis. The analysis results show that unidirectional communication patterns and static presentation materials are deemed to fail to face viral and spontaneous public audits in the digital space. As a theoretical and practical contribution, this article proposes a new model, The Spontaneous Technical Presentation Model, and recommendations for the development of a Crisis Presentation Kit for the FMCG industry. Through a theoretical approach that expands the theory of Image Restoration, this study confirms that corporate image restoration in the digital era is highly dependent on the precision and transparency of visual data presented during field qualification